Appraisal of opportunities and constraints of skin and hides marketing at Shaheed Benazirabad Division in Pakistan - Asad Ali Khaskheli; GOPANG, MANSOOR AHMED (Innovare Journal of Agricultural Sciences, 2020)
Study was carried out during the year 2017 on the appraisal of opportunities and constraints of skin and hides marketing at Shaheed Benazirabad separation. A total of 150 respondents were interviewed including 50 farmers from each districts namely Naushahro Feroze, Sanghar and Shaheed Benazirabad. The results of the present study showed fly cut followed by disease and parasites (26%, 26% and 24%) as the main production problems. In districts Naushahro Feroze, Sanghar and Shaheed Benazirabad, the major marketing problem was shortage of competitive pricing, poor assessment of transparent quality and lack of access to the market. 39%, 40% and 41% respondents said that government did not provide credit / loan, while, 45%, 47% and 44% of respondents stated that government did not provide transport facilities. 43%, 42% and 41% of respondents reported that government did not provide technical training regarding proper handling and marketing of skin and hides. 33%, 30% and 29% of the respondents stated that government provide slaughter house facility, 41%, 38% and 40% of respondents said that government provide veterinary doctor for checking quality of skin and hides, 35%, 37% and 34% of respondents argued that government provide market price in all three districts. 80%, 84% and 88% of respondents transported hides and skins by means of track. 25%, 50% and 50% of the livestock keepers sell their hides and skins to middlemen. 75%, 80%, 75% of respondents sell hides and skin at lower price when not sold in the market. 90%, 85% and 95% of the respondents used salting method for preservation of hides and skin. 60%, 40% and 60% of the respondents determined absence of flay defects criteria when they purchased hides and skin from middlemen / retailer. 100%, 80% and 100% of the respondents demanded salted skin and hides in the study area. 60%, 40% and 60% respondents believed that variation in market prices from season to season might be due to export price variation, whereas 20%, 40% and 20% argued that factory / tanner price variation / setting and wholesalers price setting was major reason for variation in market prices from season to season. Study concludes that the most prominent constraints faced by respondents are diseases, parasites and fly cuts. The major constrains faced by butcher are administrative problems, poor quality of skin and hides, storage, transportation facility.